Missouri Mathematics Project Integrated with Culture: a Solution to Enhance Student Learning Motivation - Syaifudin, Ali; Umardiyah, Fitri; Zuhriawan, M. Qoyum (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This research aims to analyze the use of the Missouri Mathematics Project learning model integrated with culture in enhancing learning motivation. The instruments used in this study are teaching modules, Jombangan batik projects, tests, and questionnaires. The subjects of the research were 32 students from SMPN 2 Perak. The research results show that Missouri Mathematics Project learning integrated with culture has a positive impact on increasing students' learning motivation. The conclusion is based on the results of the pre-test and post-test T-tests, where the significant value obtained, 0.000, is smaller than the error margin used, which is 0.05. The test results also showed high scores as a sign of increased student learning motivation.